Internal consistency and content validity of a questionnaire aimed to assess the stages of behavioral lifestyle changes in Colombian schoolchildren: The Fuprecol study (2017)
Objective To assess internal consistency and content validity of a questionnaire aimed to assess the stages of Behavioural Lifestyle Changes in a sample of school-aged children and adolescents aged 9 to 17 years-old. Methods This validation study involved 675 schoolchildren from three official school in the city of Bogota, Colombia. A self-administered questionnaire called Behavioural Lifestyle Changes has been designed to explore stages of change regarding to physical activity/exercise, fruit and vegetable consumption, alcohol abuse, tobacco use, and drug abuse. Cronbach-?, Kappa index and exploratory factor analysis were used for evaluating the internal consistency and validity of content, respectively. Results The study population consisted of 51.1% males and the participants' average age was 12.7±2.4 years-old. Behavioural Lifestyle Changes scored 0.720 (range 0.691 to 0.730) on the Cronbach ? and intra-observer reproducibility was good (Kappa=0.71). Exploratory factor analysis determined two factors (factor 1: physical activity/exercise, fruit and vegetable consumption, and factor 2: alcohol abuse tobacco use and drug abuse), explaining 67.78% of variance by the items and six interactions ?2/gL=11649.833; p and lt; 0.001. Conclusion Behavioural Lifestyle Changes Questionnaire was seen to have suitable internal consistency and validity. This instrument can be recommended, mainly within the context of primary attention for studying the stages involved in the lifestyle behavioural changes model on a school-based population.